The challenging diagnosis of granular cell tumor of the breast: a case report - Ramos, Júlia de Faria e Azevedo; Souza, Guilherme Junqueira; Tafuri, Alexandre; Ladeia, Antônio Alexandre Lisbôa; Ramos, Carlos Alberto da Silva (Mastology, 2024)
Conventional granular cell tumors, derived from Schwann cells, occur in soft tissues and are mostly benign. It is also recognized as Abrikossoff's tumor or granular cell myoblastoma, and the most common locations are found in the head, neck, arms, esophagus, and respiratory tract. The incidence in the breast is rare, representing only 8% of granular cell tumors. However, it is important to consider it as a differential diagnosis when investigating breast nodules due to its misleading presentation. This is a challenging diagnosis considering that the clinical examination and imaging workup may suggest signs of malignancy. Therefore, the lack of histopathological analysis may lead to erroneous conclusions and therapies. Due to non-specific imaging and physical examination findings, a biopsy of the lesion is mandatory for diagnosis. The tumor’s microscopic criteria consist of the presence of large polygonal cells, with eosinophilic, granular, and abundant cytoplasm. The cell borders are indistinct and the growth pattern is infiltrative, with perineural and possible perivascular involvement; however, mitotic figures are rare. The present case report demonstrates the importance of anatomopathological analysis for this diagnosis. It refers to a female patient, 28 years old, complaining of a breast node. She was followed up in the Mastology Department for further investigation, with a mammography report identifying a speculated nodule, with undefined margins, classified as Bi-Rads 5 in the right breast, and an ultrasound reporting a Bi-Rads 4C solid nodule. The clarification was made through biopsy, which determined microscopy compatible with the rare tumor of granular cells in the breast, in addition to the immunohistochemical profile, which differentiated the tumor variant of non-neural origin, composed of ovoid cells with eosinophilic granules, presenting nuclear pleomorphism, atypia, and mitotic figures.